[INVITED] Slab plasmonic platforms combined with Plastic Optical Fibers and Molecularly Imprinted Polymers for chemical sensing. (November 2018) - Zeni, Luigi; Pesavento, Maria; Marchetti, Simone; Cennamo, Nunzio
Highlights: Low-cost plasmonic platform tested to monitor MIP-small molecule interaction. MIP receptor layers easily formed by in situ polymerization on SPR slab waveguide. Light injected in the slab by a trench in a purposely designed holder. SPR slab sensor performances similar to other low-cost plasmonic platforms. MIP-SPR sensor obtained by an easier, faster and more reproducible procedure. Abstract: A novel low-cost surface plasmon resonance (SPR) platform has been tested, for the first time, to monitor the interaction between a molecularly imprinted polymer (MIP) and a small molecule as the substrate. As a proof of principle, the considered MIP was specific for furfural (2-FAL, MW = 96.4), so that the possibility of using the new device for detection of 2-FAL in aqueous media was investigated. For the sake of comparison a sensor based on the same MIP specific for 2-FAL deposited on an SPR platform in a D-shaped plastic optical fiber (POF), which has been previously demonstrated to well perform for different analytes, has been considered too. The experimental results showed good performances of the novel platform for chemical sensing based on MIP as receptor in terms of selectivity, sensitivity and figure of merit (FOM). The limit of detection (LOD) of this simple and low-cost SPR sensor system is about 0.03 ppm, completely comparable to that of previously proposed devices based on SPR in a D-shaped POF (about 0.05 ppm), but with the advantage of an easier and more reproducible preparation procedure.